Immunogenicity and Protective Efficacy against Murine Tuberculosis of a Prime-Boost Regimen with BCG and a DNA Vaccine Expressing ESAT-6 and Ag85A Fusion Protein - Jia Lu; Chun Wang; Zhiguang Zhou; Ying Zhang; Tingting Cao; Chunwei Shi; Zhenhua Chen; Lingxia Chen; Changxue Cai; Xionglin Fan (Clinical and Developmental Immunology)
Heterologous prime-boost regimens utilizing BCG as a prime vaccine probably represent the best hope for the development of novel tuberculosis (TB) vaccines. In this study, we examined the immunogenicity and protective efficacy of DNA vaccine (pcD685A) expressing the fusion protein of Ag85A and ESAT-6 (r685A) and its booster effects in BCG-immunized mice. The recombinant r685A fusion protein stimulated higher level of antigen-specific IFN-γ release in tuberculin skin test- (TST-) positive healthy household contacts of active pulmonary TB patients than that in TST-negative population. Vaccination of C57BL/6 mice with pcD685A resulted in significant protection against challenge with virulent Mycobacterium tuberculosis H37Rv when compared with the control group. Most importantly, pcD685A could act as a BCG booster and amplify Th1-type cell-mediated immunity in the lung of BCG-vaccinated mice as shown the increased expression of IFN-γ. The most significant reduction in bacterial load of both spleen and lung was obtained in mice vaccinated with BCG prime and pcD685A DNA booster when compared with BCG or pcD685A alone. Thus, our study indicates that pcD685A may be an efficient booster vaccine against TB with a strong ability to enhance prior BCG immunity.